Optimalisasi Inovasi Produk Makanan Berbahan Dasar Jamur sebagai Upaya Penguatan Wanita Tani Jamur melalui Pelatihan dan Pendampingan - Nova Ariyanto; Nisa Adelia Trianita; Urzha Dian Syafitiri; Arfido Ramadhani; Sutarno Sutarno; Akhmad Sholakhudin; Tuffahati Sahna Khumairah; Riki Apriyanto; Berliana Putri; Nur Khilya Maulida; Meisya Maulida Khusna; Isna Nur Aini; Tegar Saputra; M. Warisa Al Malik; Ulfatul Elsa Muzayyanah; Setia Iriyanto; Ahmad Ilham (Jurnal Surya Masyarakat, 2024)
Genting Village, Semarang, has great potential for mushroom cultivation thanks to geographical and climatic conditions that favour healthy mushroom growth. Although farm women have been actively involved in mushroom cultivation in this village, they often face obstacles in terms of access to resources, knowledge, and marketing of mushroom-based processed food products. To overcome this problem, we, UKM Hizbul Wathan, in the PPK Ormawa 2023 grant activity, propose training and mentoring in the manufacture and marketing of mushroom-based food in Genting Village. The method we use is SWOT analysis, used to identify strengths, weaknesses, threats, and development strategies in overcoming the problems of the mushroom farmer women's group in Genting Village. Strengths include favourable geographical conditions for mushroom cultivation, participation of women farmers, and unique local wisdom. Meanwhile, the main weaknesses are limited access to resources and knowledge. Opportunities in diversification of mushroom-based food products and increasing consumer awareness about healthy food should be utilised. Threats include market competition and climate change. The discussion focuses on strategies for developing training programmes to improve farm women's knowledge and skills, effective marketing efforts, and partnership opportunities with external parties. The results of this study show that mentoring and training in mushroom-based food processing can create new economic opportunities, increase the income of farm women, and support sustainable development in Genting Village.